2012
DOI: 10.1016/j.ihj.2012.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Choice of an alternative lead for QT interval measurement in serial ECGs when Lead II is not suitable for analysis

Abstract: When QT interval cannot be measured in Lead II, the best alternative leads are aVR, aVF, V5, V6 and V4 in that sequence. It differs maximally from that in Lead II in Lead aVL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…The ECG complex(es) used for interval measurement is not uniform and differs between core laboratories. When using a single lead for analysis, controversy exists as to which lead or leads to utilize for measurement since the QT interval can vary by over 20 ms within a single lead or between leads in a 10 s tracing even in the presence of stable sinus rhythm [45]. Furthermore, an individual’s QT and QTc demonstrates diurnal variability with the longest values occurring during sleep and the shortest values occurring during the day.…”
Section: Measurement Of the Qt Intervalmentioning
confidence: 99%
“…The ECG complex(es) used for interval measurement is not uniform and differs between core laboratories. When using a single lead for analysis, controversy exists as to which lead or leads to utilize for measurement since the QT interval can vary by over 20 ms within a single lead or between leads in a 10 s tracing even in the presence of stable sinus rhythm [45]. Furthermore, an individual’s QT and QTc demonstrates diurnal variability with the longest values occurring during sleep and the shortest values occurring during the day.…”
Section: Measurement Of the Qt Intervalmentioning
confidence: 99%
“…This difference in ECG configurations can affect the morphology and some measurements of ECG parameters measured here. A previous study reported ~7 ms difference in QT intervals of patients measured from the two ECG leads (Salvi et al, 2012). However, this relatively small lead‐based difference is unlikely to change the larger anesthesia‐ and DOX‐induced ECG modulation reported in this study.…”
Section: Discussionmentioning
confidence: 94%
“…Lead I is frequently adequate for interpretation and the QTc measurement from lead I has been shown to differ by an average of 7.5 ms from that obtained from lead II. 12 Various ECG vectors, including lead II, can be obtained by both the Apple Watch and Kardia Pro devices by repositioning the device on the patient’s body. 13 Accordingly, single-lead mobile cardiac outpatient telemetry units have previously been approved by the United States Federal Drug Administration for QTc measurement.…”
Section: Discussionmentioning
confidence: 99%